Anti-trichomonad activities of different compounds from foods, marine products, and medicinal plants: a review - Mendel Friedman; Christina C. Tam; Luisa W. Cheng; Kirkwood M. Land (BMC, 2020)
Abstract Human trichomoniasis, caused by the pathogenic parasitic protozoan Trichomonas vaginalis, is the most common non-viral sexually transmitted disease that contributes to reproductive morbidity in affected women and possibly to prostate cancer in men. Tritrichomonas foetus strains cause the disease trichomoniasis in farm animals (cattle, bulls, pigs) and diarrhea in domestic animals (cats and dogs). Because some T. vaginalis strains have become resistant to the widely used drug metronidazole, there is a need to develop alternative treatments, based on safe natural products that have the potential to replace and/or enhance the activity of lower doses of metronidazole. To help meet this need, this overview collates and interprets worldwide reported studies on the efficacy of structurally different classes of food, marine, and medicinal plant extracts and some of their bioactive pure compounds against T. vaginalis and T. foetus in vitro and in infected mice and women. Active food extracts include potato peels and their glycoalkaloids α-chaconine and α-solanine, caffeic and chlorogenic acids, and quercetin; the tomato glycoalkaloid α-tomatine; theaflavin-rich black tea extracts and bioactive theaflavins; plant essential oils and their compounds (+)-α-bisabolol and eugenol; the grape skin compound resveratrol; the kidney bean lectin, marine extracts from algae, seaweeds, and fungi and compounds that are derived from fungi; medicinal extracts and about 30 isolated pure compounds. Also covered are the inactivation of drug-resistant T. vaginalis and T. foetus strains by sensitized light; anti-trichomonad effects in mice and women; beneficial effects of probiotics in women; and mechanisms that govern cell death. The summarized findings will hopefully stimulate additional research, including molecular-mechanism-guided inactivations and human clinical studies, that will help ameliorate adverse effects of pathogenic protozoa.